ANALISIS KEMAMPUAN NUMERASI DALAM MENYELESAIKAN SOAL PADA SISWA SMP NEGERI 1 CIAMIS DITINJAU DARI SELF-EFFICACY - Anggraini, Devi; Prabawati, Mega Nur; Herawati, Linda (LPPM Universitas Bina Bangsa, 2024)
This research aims to describe the ability of class VIII students at SMP Negeri 1 Ciamis in solving mathematics problems on SPLDV material based on the self-efficacy category. The research methodology used is descriptive qualitative research. The research subjects in this study were 30 students in class VIII-E of SMP Negeri 1 Ciamis. The data collection technique is a purposive sampling technique which begins with students filling out the self-efficacy questionnaire twice at different times, then filling in the numeracy ability test questions, and after that an interview is conducted. The results of this research are that students who have high self-efficacy will fulfill 3 indicators of numeracy ability and solve questions easily. Students who have moderate self-efficacy will fulfill 3 indicators of numeracy ability but when solving mathematics problems they have obstacles and experience a few errors in using formulas. Students who have low self-efficacy only fulfill 2 indicators of numeracy ability and cannot solve math problems to completion